Male and Female Language: Sociolinguistics in 'Wolf Gold' WhatsApp Chat - Artika, Mutiara Romi; Sofilla, Devi; Handyanto, Wina Avrillia; Nisa, Khairun; Rangkuti, Rahmadsyah (Linguistics and ELT Journal, 2024)
This research analyzes “Wolf Gold’ group chat using a sociolingustics gender language difference by Lakoff and Coates Theory. The researchers uses a qualitative descriptive method and presented with tables. The author found out that in Lakoff’s features in women’s language include hedges, tag questions, empty adjectives, intensifiers, superpolite forms, and avoidance of strong swear words. In men’s language, based on Coates’ theory, swearing, commands, declaratives, and interruptions were observed. While women used most of Lakoff’s features, some were absent due to the chat’s context. Men mostly used swearing, but both genders showed overlap in using features from the opposite theory, highlighting inconsistencies in applying Lakoff’s and Coates’ theories across different gender. The theories of Lakoff and Coates show inconsistencies, as features of men’s language appear in women’s speech and vice versa.